MAIN AREAS OF CONSULTING IN THE FIELD OF IMPLEMENTATION, USE AND IMPROVEMENT OF ACCOUNTING SOFTWARE COMPLEXES (Economic journal of Lesya Ukrainka Volyn National University, 2022)
In the Ukrainian market of information systems in audit Russian technologies have been leading for a long time in terms of coverage volume. However, due to the impossibility of using the products of the aggressor country, businesses are looking for alternative solutions, and therefore need qualified consulting processes, assistance in choosing software with the appropriate set of functions, adaptation to additional legislation and specifics of the enterprise. The purpose and objectives of the article is to define the main methodological principles of consulting in the field of implementation and improvement of accounting software packages, to systematize information on alternative technological solutions in terms of compliance with the selected evaluation criteria. The article defines the essence of counseling, provides a classification of types of consulting, on the basis of duration. According to the authors, consultations are divided into one-time, intensive consultations, consulting support and audit. Consulting in the field of work with accounting software packages is a special consultation. According to the authors, information technology in accounting is a set of software and hardware designed to collect, process, accumulate, transmit, process information attended by an accountant with the possibility of transformation to the needs of other users. The strengths and weaknesses of these categories of professionals from the point of view of service consumers are considered and the best option for cooperation is found. Business inquiries are to abandon Russian software products, finding a similar replacement in terms of functions. Therefore, the authors considered the definition of the main criteria for evaluating accounting software packages to be an important area of research. The authors of the article offer to evaluate the functionality, localization, location (On-Premise or On-Cloud), the ability to transfer information from one database to another, the price segment, the availability of qualitative support. Based on these criteria, the authors created a matrix of compliance of accounting software packages, helping the consultant to test the program beforehand, prepare a consultation plan and one or more programs that meet the requirements and get the specifics of the activity.
Keywords: Consulting, consultant, information technologies in accounting, consultant competence, one-time consultation, intensive consultation, consulting support, audit